[rac-1,8-Bis(2-carbamoylethyl)-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane]copper(II) diacetate tetrahydrate: crystal structure and Hirshfeld surface analysis - Yasmin, S.; Rabi, S.; Chakraborty, A.; Kwong, Huey Chong *; Tiekink, Edward R. T. *; Roy, T. G. (International Union of Crystallography, 2021)
The title CuII macrocyclic complex salt tetrahydrate, [Cu(C22H46N6O2)](C2H3O2)2·4H2O, sees the metal atom located on a centre of inversion and coordinated within a 4 + 2 (N4O2) tetragonally distorted coordination geometry; the N atoms are derived from the macrocycle and the O atoms from weakly associated [3.2048 (15) Å] acetate anions. Further stability to the three-ion aggregate is provided by intramolecular amine-N—H...O(carboxylate) hydrogen bonds. Hydrogen bonding is also prominent in the molecular packing with amide-N—H...O(amide) interactions, leading to eight-membered {...HNCO}2 synthons, amide-N—H...O(water), water-O—H...O(carboxylate) and water-O—H...O(water) hydrogen bonds featuring within the three-dimensional architecture. The calculated Hirshfeld surfaces for the individual components of the asymmetric unit differentiate the water molecules owing to their distinctive supramolecular association. For each of the anion and cation, H...H contacts predominate (50.7 and 65.2%, respectively) followed by H...O/O...H contacts (44.5 and 29.9%, respectively).